Hydrotreating rice bran oil for biofuel production - Salwa A. El Khatib; Samia A. Hanafi; Youssef Barakat; Eslam F. Al-Amrousi (Egyptian Journal of Petroleum)
Hydrotreating technique is one of the most promising method for producing high quality of biofuels from plant oils. Here, the non-esculent rice bran oil was subjected to hydrotreatment in a high pressure cata-test unit, using sulfided NiMo/Al2O3, catalyst, under various pressures, temperatures and liquid hourly space velocities. The influence of each of these factors on the qualities and quantities of the acquired products was investigated, and the operating conditions were optimized. Evaluation of the final product was made on basis of its fuel characteristics, and compared with those of the raw oil. The results revealed the significant improvement of the physicochemical properties of the hydrotreated product to become very close, or may be better than those derived from petroleum sources. Keywords: Biofuel, Hydrotreating, Rice bran oil